CalMHSA Student Mental Health Campus-Wide Survey 2013 Summary Report - Sontag-Padilla, Lisa (RAND Corporation, 2014)
Report provides the results of a California survey of colleges and universities on mental health experiences and attitudes, perceptions of campus mental health services, and perceptions of overall campus climate toward mental health and well-being.